Odpowiedzi

2010-01-05T23:44:59+01:00
A). 2(3x+4)-3(5x-6)+4(7x+8)=115
6x+8-15x+18+28x+32x=115
19x+58=115
19x=57:19
x=3

b). x (x-5) -x (x+4) = -63
2x-5x-2x-4x=-63
-9x=-63:-9
x=7

1 4 1
Najlepsza Odpowiedź!
2010-01-05T23:55:27+01:00
A)
2 (3x+4) -3 (5x-6) +4 (7x+8) = 115
6x + 8 -15x + 18 + 28x +32 = 115
19x + 58 = 115
19x = 115- 58
19x = 57
x = 57 : -19
x = 3


b) x (x-5) -x (x+4) = -63
x² -5x - x² -4x = -63
-9x = -63
x = (-63): (-9)
x = 7

c) 4 (x-3) 2 = -6 chyba ze jest inny zapis ( coś z 2 po nawiasie??
(4x - 12 )*2 = -6
8x -24 = -6
8x = -6 + 24
8 x = 18
x = 18 : 8
x = 9/4


d) 30-10 (2-3x) = -50
30 - 20 +30x = -50
10 +30x = -50
30x = -50 -10
30x = -60
x = (-60) : 30
x = -2

e) 6x-7 (11+2x) +2 = - 4 (15-x) +3x
6x -77 -14x +2 = -60 +4 x + 3x
-8x - 75 = -60 + 7x
-8x -7x = -60 +75
-15x = 15
x = 15 : (-15)
x = - 1
2 2 2